Effectiveness of Virtual Pharmacist-Led Smoking Cessation Support in a Secondary Care Hospital in Islamabad (Journal of Asian Development Studies, 2025)
Globally, smoking is a significant public health concern that requires innovative cessation interventions. Virtual pharmacist-led programs can provide accessible support, particularly in settings without dedicated services. This study evaluates a virtual pharmacist-led intervention's impact on smoking cessation, medication adherence, and patient engagement. A quasi experimental pre-post study was conducted in a secondary care hospital in Islamabad, Pakistan, with 80 adult smokers (≥18 years, ≥5 cigarettes/day for a year) willing to quit. The three-month program included weekly teleconsultations, pharmacotherapy guidance, behavioral counselling, and automated text support. Post-intervention, 60% achieved 7-day abstinence (p